UNDP's 1996 report on human development in Bangladesh : a pro-poor agenda ; volume 3 poor people's perspectives (Dhaka : UNDP, 1996)
Economics
Keywords: Human Development; Human development-Report; Pro-poor governance; Poor communities; Poverty